Ciudad, mujer y conflicto : el comercio ambulante en el D.F. - Lezama, José Luis (El Colegio de México A.C., 1991)
The author describes the general socioeconomic characteristics of a group of itinerant saleswomen in the Historical Center of Mexico City, within the sociopolitical framework of itinerant trade in Mexico City. The first part entails a presentation of the theme "women and work". Following is a discussion of problems affecting those most directly involved in itinerant trade in Mexico City. Lastly, Lezama offers a description and review of the general characteristics of women engaged in this activity.